2020
DOI: 10.1111/cgf.13970
|View full text |Cite
|
Sign up to set email alerts
|

QUESTO: Interactive Construction of Objective Functions for Classification Tasks

Abstract: Building effective classifiers requires providing the modeling algorithms with information about the training data and modeling goals in order to create a model that makes proper tradeoffs. Machine learning algorithms allow for flexible specification of such meta‐information through the design of the objective functions that they solve. However, such objective functions are hard for users to specify as they are a specific mathematical formulation of their intents. In this paper, we present an approach that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Additionally, when domain-specific inaccuracies or discrepancies are found in the outputs of these models, user feedback is often used to incrementally adapt the models to be better-suited to specific domains or decisions. Recently, Das et al 8 presented the concept of interactive objective functions as the method for this user feedback to be incorporated. Their approach allows users to specify particular aspects of the model and data that are important for the task or domain, which are then translated into constraints of the objective function used to generate and select models through the use of AutoML techniques.…”
Section: Visualization Is Crucial For Human Acency In Aimentioning
confidence: 99%
“…Additionally, when domain-specific inaccuracies or discrepancies are found in the outputs of these models, user feedback is often used to incrementally adapt the models to be better-suited to specific domains or decisions. Recently, Das et al 8 presented the concept of interactive objective functions as the method for this user feedback to be incorporated. Their approach allows users to specify particular aspects of the model and data that are important for the task or domain, which are then translated into constraints of the objective function used to generate and select models through the use of AutoML techniques.…”
Section: Visualization Is Crucial For Human Acency In Aimentioning
confidence: 99%
“…Others have analysed variety in pareto-optimal solutions in multiobjective optimization functions [69], [70]. While none of these approaches allowed users to express specifications in objective functions interactively, Das et al prototyped QUESTO, allowing users to interactively create objective functions to select optimal classifiers trained on tabular data [7]. Unlike QUESTO, in this paper we seek to extend research on interactive objective functions by showing users conflicts in objectives as opposed to allowing interactive creation of objective functions.…”
Section: User Preferences In Objective Functionsmentioning
confidence: 99%
“…These VA systems use models that are driven by an objective function as designed by an expert ML practitioner or a data scientist to achieve a desired data analytic goal, such as correctly predicting class labels of unseen data, or predict a quantitative value etc. Recently, Das et al have demonstrated a VA system, QUESTO [7] that facilitated interactive creation of objective functions to solve a classification task utilising an Auto-ML system. While their approach helped users to interactively explore and express a wide array of objectives to an objective function, the authors discussed potential conflicts that may occur in interactive specification of objectives as a limitation to QUESTO's workflow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations